Functional characteristics of novel pancreatic Pax6 regulatory elements. (10th August 2018) - Buckle, Adam; Nozawa, Ryu-suke; Kleinjan, Dirk A; Gilbert, Nick
Abstract: Complex diseases, such as diabetes, are influenced by comprehensive transcriptional networks. Genome-wide association studies have revealed that variants located in regulatory elements for pancreatic transcription factors are linked to diabetes, including those functionally linked to the paired box transcription factor Pax6. Pax6 deletions in adult mice cause rapid onset of classic diabetes, but the full spectrum of pancreatic Pax6 regulators is unknown. Using a regulatory element discovery approach, we identified two novel Pax6 pancreatic cis -regulatory elements in a poorly characterized regulatory desert. Both new elements, Pax6 pancreas cis -regulatory element 3 (PE3) and PE4, are located 50 and 100 kb upstream and interact with different parts of the Pax6 promoter and nearby non-coding RNAs. They drive expression in the developing pancreas and brain and code for multiple pancreas-related transcription factor-binding sites. PE3 binds CCCTC-binding factor (CTCF) and is marked by stem cell identity markers in embryonic stem cells, whilst a common variant located in the PE4 element affects binding of Pax4, a known pancreatic regulator, altering Pax6 gene expression. To determine the ability of these elements to regulate gene expression, synthetic transcriptional activators and repressors were targeted to PE3 and PE4, modulating Pax6 gene expression, as well as influencing neighbouring genes and long non-coding RNAs, implicating the Pax6 locus in pancreas function and diabetes.